The Transgender Bathroom Problem: A Critical Discourse Analysis of Public Opinions from News Sites - Andi Priyowicaksono (Jurnal Bahasa, Sastra, dan Studi Amerika, 2020)
This research seeks to investigate public reaction towards the ordinance that allowed transgender people to use bathroom in correspondence to their identified gender. The article explores the reaction through observing comments expressed by public in comment sections of news articles from Abcnews (abcnews.com), Usatoday (usatoday.com), and Washington Post (washingtonpost.com). Comments expressed by public in the comment section contain their own belief and ideology which often clashes with one another. The conflict resulted in the verbal interchange of ideas (discourse) that are expressed through agreements and arguments. Drawing on qualitative method, this paper critically analyzes these discourses appearing in the comment section. The commenters’ belief in the context of transgender bathroom ordinance is correlated with the work of Michel Foucault that put focus on the systematical relation between power and its subject(s). This paper argues that heteronormativity is the power driving the subjects in reacting to the case of transgender bathroom ordinance.